Can we participate in global value chains in the dark? An empirical study in Africa - Moteng, Ghislain; Sikadi, Djamila Piameu; Oumbe, Honoré Tekam; Kengne, Arnold Foko (Quantitative Economics and Management Studies, 2025)
This study analyses the effect of electricity access on participation in global value chains (GVCs) in 41 African countries between 1990 and 2018. By mobilizing static (fixed effects) and dynamic (two-stage GMM) panel methods, the results show that better access to electricity significantly favours integration into GVCs. The effect remains robust to different measures of electrification and GVC participation. The results also highlight that disparities in access to electricity between urban and rural areas can reinforce unequal integration into global value chains, and that participation is largely determined by the use of fossil fuels. Based on these findings, the study recommends investing in inclusive and sustainable electrification, particularly in rural and industrial areas, and establishing green regulatory frameworks to encourage the adoption of cleaner energies.